1994
DOI: 10.1152/jn.1994.72.6.2570
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of potassium by nonmyelinating Schwann cells induced by axonal activity

Abstract: 1. The electrophysiological properties of the rabbit vagus nerve (membrane potential, compound action potentials, and afterpotentials) and potassium accumulation were measured simultaneously during low-frequency stimulation (LFS) (0.5 and 1 Hz) by using a modified sucrose-gap apparatus and potassium-sensitive microelectrodes (KSM). 2. During LFS at 0.5 and 1 Hz, the concentration of K+ in the extracellular space ([K+]c) increased in approximately 30 s to a maximal level that was 0.6 and 1.5 mM, respectively, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…Typically, the inter-diffusion between compartments is minimized by applying grease around the preparation at points which traverse between the compartments; however, the quality of this insulation remains low (discussed in Mert, 2007), and the grease insulation is not compact enough to suit short WM strips. Rubber membranes with holes closely matching the preparations proved highly efficient in earlier sucrose gap experiments (Berger, 1963;Boev and Golenhofen, 1974;Cleemann and Suenson, 1984;Hoyle, 1987), including studies on most challenging C-fibers in peripheral nerves, which require higher stimulation intensities and shorter conduction distances (Jirounek et al, 1991;Gaumann et al, 1992;Robert and Jirounek, 1994;Erne-Brand et al, 1999;Dalle et al, 2001). In this paper we designed and tested a DSG apparatus with rubber membrane separation of the compartments that enhances the conditions for recording and analysis of CAPs and by virtue of the compactness of the compartments is ideally designed to accommodate relatively short preparations such as those derived from rat and mouse spinal cords.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, the inter-diffusion between compartments is minimized by applying grease around the preparation at points which traverse between the compartments; however, the quality of this insulation remains low (discussed in Mert, 2007), and the grease insulation is not compact enough to suit short WM strips. Rubber membranes with holes closely matching the preparations proved highly efficient in earlier sucrose gap experiments (Berger, 1963;Boev and Golenhofen, 1974;Cleemann and Suenson, 1984;Hoyle, 1987), including studies on most challenging C-fibers in peripheral nerves, which require higher stimulation intensities and shorter conduction distances (Jirounek et al, 1991;Gaumann et al, 1992;Robert and Jirounek, 1994;Erne-Brand et al, 1999;Dalle et al, 2001). In this paper we designed and tested a DSG apparatus with rubber membrane separation of the compartments that enhances the conditions for recording and analysis of CAPs and by virtue of the compactness of the compartments is ideally designed to accommodate relatively short preparations such as those derived from rat and mouse spinal cords.…”
Section: Discussionmentioning
confidence: 99%
“…Studying slowly conducting non-myelinated axons, like C-fibers of peripheral nerves, by CAP recording (Jirounek et al, 1991;Gaumann et al, 1992;Robert and Jirounek, 1994;Erne-Brand et al, 1999;Dalle et al, 2001), requires short conduction distances because of increased temporal dispersion of action potential arrival times in individual non-myelinated axons with increased distance. The use of 3.5 mm-wide ACSF module in our experiments on Shiverer mice presented here provided sufficient synchrony to detect the slow multi-component C-wave reflecting action potential propagation in dysmyelinated axons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This proximity between ESCs and C fibers provides a structural basis by which cellular events occurring in ESCs could modify the excitability of these nociceptors. This may occur in part by ESCs buffering extracellular K ϩ in the axonal environment (Robert and Jirounek, 1994) and regulating lipid metabolism (Fullerton et al, 1998).…”
Section: Peripheral Glia As Transducers Of Nociceptive Informationmentioning
confidence: 99%
“…The pump has a lower affinity for intracellu- Robert and Jirounek, 1994 lar Na ϩ so that it is stimulated by increases in Na i in the physiological range. In contrast, studies on the functioning of the Na ϩ pump on glial cells have shown that the functional affinity for K e is much lower so that the pump is stimulated by increases in K e in the physiological and pathological ranges (Ballanyi et al, 1987;Ballanyi and Kettenmann, 1990;Coles et al, 1986;Reichenbach et al, 1992;Walz et al, 1983).…”
Section: Net Uptake Of K ؉ By the Na ؉ Pumpmentioning
confidence: 99%